PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA MATA PELAJARAN PKn - ., Adriana; Thomas, Yosef; ., Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The purpose of this study to determine the design implementation jigsaw cooperative learning model, to increase the activity belaajar learners and learning outcomes PKn. Prior to the implementation of measures average student active 5 people or 20.00%. After the implementation of the measures the average first cycle rising to 11 students or 44.00% and after the implementation of the second cycle of the average rose again to 16 students or 64.00% pserta . While the acquisition of learning outcomes of students prior to the implementation of the action shows learners who completed only 10 learners or only 40.00% of the total number of students, and after the first cycle of implementation actions are completed enrollment increased to 16 students or 64.00%, whereas after the implementation of the second cycle of learners who completed increased to 20 students or 80.00%. use a jigsaw cooperative learning model can improve learners' learning activities and the acquisition of learning outcomes of students in learning PKn. Keyword: Jigsaw Learning Model Type Abstrak: Tujuan penelitian ini untuk mengetahui rancangan pelaksanaan model pembelajaran kooperatif tipe jigsaw, untuk meningkatkan aktivitas belaajar peserta didik dan hasil belajar PKn. Sebelum pelaksanaan tindakan rata-rata siswa aktif 5 orang atau 20.00%. Setelah pelaksanaan tindakan siklus I rata-ratanya naiknya menjadi 11 orang peserta didik atau 44,00% dan setelah pelaksanaan tindakan siklus II rata-ratanya naik lagi menjadi 16 orang pserta didik atau 64,00%. Sedangkan perolehan hasil belajar peserta didik sebelum pelaksanaan tindakan menunjukkan peserta didik yang tuntas hanya 10 orang peserta didik atau hanyaÂ 40,00% dari jumlah siswa, dan setelah pelaksanaan tindakan siklus I jumlah peserta didik yang tuntas meningkat menjadi 16 orang peserta didikÂ atau 64,00%, sedangkan setelah pelaksanaan tindakan siklus II peserta didik yang tuntas meningkat lagi menjadi 20 orang peserta didik atau 80,00 %. penggunaan model pembelajaran kooperatif tipe jigsaw dapat meningkatkan aktivitas belajar peserta didik dan perolehan hasil belajar peserta didik dalam pembelajaran PKn. Kata Kunci: Model Pembelajaran Tipe Jigsaw